Improving the anti-ovarian cancer activity of docetaxel with biodegradable self-assembly micelles through various evaluations. (June 2015) - Gao, Xiang; Wang, Shimin; Wang, BiLan; Deng, Senyi; Liu, Xiaoxiao; Zhang, XiaoNing; Luo, LinLi; Fan, RangRang; Xiang, MingLi; You, Chao; Wei, YuQuan; Qian, ZhiYong; et al.
Abstract: Docetaxel (DOC) produces anti-tumor effects by inducing apoptosis and inhibiting cell growth. However, its clinical application is limited by its hydrophobicity and low biocompatibility. Therefore, improving DOC's water solubility, biocompatibility, and anti-tumor effects are important goals that will improve its clinical utility. In this work, DOC and methoxy poly(ethylene glycol) (MPEG)/polycaprolactone (PCL) (MPEG-PCL) showed good compatibility through computer simulations. We prepared DOC-loaded polymeric micelles (DOC/MPEG-PCL micelles) with drug loading of 6.82% and encapsulation efficiency of 98.36%; these were monodispersed and approximately 30 nm in diameter, and released DOC over an extended period in vitro and in vivo. In addition, DOC/MPEG-PCL micelles inhibited cell growth and induced apoptosis more effectively than free DOC in vitro. Furthermore, DOC/MPEG-PCL micelles inhibited ovarian tumor growth more significantly than free DOC. Immunohistochemical analysis indicated that DOC/MPEG-PCL micelles improved DOC's anti-tumor effect by enhancing tumor cell apoptosis and suppressing tumor cell proliferation. Moreover, in bio-imaging analysis, DOC/MPEG-PCL micelles showed a higher concentration and a longer retention time in ovarian tumor tissue than did free DOC, indicating that the DOC/MPEG-PCL micelles delivered more anti-tumor drug to the tumor. Our data suggest that DOC/MPEG-PCL micelles have the potential to be applied clinically in ovarian cancer therapy.